Assessment of Hepatoprotective Activity of Hyptis capitata Jacq. Against Oxidative Stress Induced by H2O2 (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Medicinal plants occupy a key position in maintaining the health of the human population. Hyptis capitata Jacq. is an exotic ethnomedicinal plant of Lamiaceae possessing immense potential. The present study was carried out to assess the in vitro hepatoprotective activity of methanolic leaf extract of H. capitata against H2O2 induced oxidative stress in HepG2 cell lines. Total antioxidant capacity and Superoxide radical scavenging activity of the extract were also performed. The extract displayed considerable free radical scavenging activity (P < 0.01). MTT assay was used to assess the in vitro hepatoprotective activity in HepG2 cell lines. The extract displayed concentration-dependent cell viability with maximum protection (63.97 ± 1.23%) in H2O2 induced HepG2 cell lines at 100 μgml-1. H. capitata is a promising herb with significant antioxidant and hepatoprotective potential.